Socio-Economic Aspects of Urban Grant Cancellation: Examining Religious Court's Decision on Grant Cancellation - Harahap, Purnama Hidayah; Asmuni, Asmuni; Syahputra, Akmaluddin (Madania: Jurnal Kajian Keislaman, 2023)
This study aimed to look at socio-economic aspects of grant cancellation in urban communities by analyzing the considerations of the Medan Religious Court judge. This research was a normative legal research by analyzing decision No: 887/Pdt.G/2009/PA. Mdn and decision No. 249/Pdt.G/2010/PA. Mdn uses the theory of maslahah. The results of this study showed that the judge, in giving the decision to cancel the grant, does not consider socio-economic aspects; the judge looks more at formal considerations only. The social aspect that occurred in the year of the acquisition of property was not taken into consideration by the judge; this was very detrimental for those who acquired property before 1974 and also for those who did not have sufficient access to information regarding formal requirements. On the other hand, the judge also did not consider how long the property was managed; some assets had been managed for years and had high economic value. Of course, this can be detrimental to those who have acquired the property for many years and have managed it. However, due to limited knowledge of formal requirements, the property can be manipulated into dispute. Even though socially, the property has been owned for many years and used by the community. Penelitian ini bertujuan untuk melihat aspek sosio-ekonomi pembatalan hibah di masyarakat perkotaan dengan menganalisis pertimbangan hakim Pengadilan Agama Medan. Penelitian ini merupakan penelitian hukum normatif dengan menganalisis putusan No: 887/Pdt.G/2009/PA.Mdn dan putusan No. 249/Pdt.G/2010/PA.Mdn menggunakan teori maslahah. Hasil penelitian ini menunjukkan bahwa hakim dalam memberikan putusan pembatalan hibah tidak mempertimbangkan aspek sosia-ekonomi; hakim lebih melihat pertimbangan formal saja. Aspek sosial yang terjadi pada tahun perolehan hibah tidak dipertimbangkan oleh hakim; Ini sangat merugikan bagi mereka yang memperoleh hibah sebelum tahun 1974 dan juga bagi mereka yang tidak memiliki akses yang cukup terhadap informasi mengenai persyaratan formal. Di sisi lain, hakim juga tidak mempertimbangkan berapa lama hibah itu dikelola. Beberapa aset telah dikelola selama bertahun-tahun dan memiliki nilai ekonomi tinggi. Tentu saja, ini dapat merugikan mereka yang telah memperoleh hibah selama bertahun-tahun dan telah mengelolanya. Namun, karena pengetahuan yang terbatas tentang persyaratan formal, hibah sering dimanipulasi menjadi sengketa. Padahal secara sosial, hibah tersebut telah dimiliki selama bertahun-tahun dan digunakan oleh masyarakat.